Heroes of the energy front - Kukharyk, Roman; Zinkevych, Petro (My University, 2023)
Introduction. Distribution networks (Oblenergo), trunk networks (Ukrenergo) and generation facilities (CHP, TPP, HPP) were the main target of artillery and missile attacks by the Russian Federation. As a result of shelling in the system, 50% of the country's electrical networks were damaged. Results and discussion. The northern, southern, eastern and western regions suffered the greatest damage. During the war, the following electrical distribution networks (oblenergo) were damaged as a result of artillery shelling: 1. Dtek Kyiv Regional Power Grids; 2. DTEK Donetsk power grids; 3. "Kharkivoblenergo" JSC; 4. "Khersonoblenergo" JSC; 5. JSC "Mykolaivoblenergo"; 6. PJSC "Zaporizhjiaoblenergo"; 7. JSC "Chernihivoblenergo"; 8. Sumioblenergo JSC. Damage to main electrical networks (UKRENERGO): The northern, southern, eastern and western regions suffered the greatest damage. About 30 substations of various voltages were damaged.
Keywords: кафедра електропостачання і енергоменеджменту; renewal of electricity; damage to electrical lines; energy; поновлення електроенергії; пошкодження електричних ліній; енергія